Ethnicity and Development Issues in Nigeria - Obire, Mathias Oghenetejiri; Chiemeke, Stephen Chukwunonso (Kashere Journal of Politics and International Relations, 2025)
Nigeria is a multi-ethnic nation-state with socio-cultural differences among its component ethnic groups all of which have resulted into cultural dissimilarities. These cultural dissimilarities have been established by the variances in culture which include language, dress, diet and types of social system. The ethnic virus has been one of the most important causes of social crisis and political instability in Nigeria; and ethnicity has been perceived in general as a major obstacle to the overall politico-economic development of the country. Although every nation has its own peculiar ethnic issues, the difference is the mechanism by which the challenges are managed or ameliorated. The ethnic conundrum remains a major obstacle to Nigeria’s existence as nation state. Consequences of ethnicity include communal conflict, political violence, nepotism/discrimination, underdevelopment, waste of manpower, political instability, disunity and disloyalty to the nation. Primordial and instrumental theories were used to give a vivid insight of ethnicity in this paper. It asserts that the concept of ethnicity and tribe never appeared in the political dictionary of most developed countries and this helped to build a virile national economy for these states. Their systems of government worked since they enjoyed the full loyalty of their people at the center unlike Nigeria where allegiance is more to the component units. A re-engineering of the country is needed to make it workable. Devolution of power to the regions is necessary.